Impact of SARS-Con-V2 on the Poultry Industry in Kuwait: A Case Study - Al-Khalaifah, Hanan; Al-Nasser, Afaf; Abdulmalek, Noura; Al-Mansour, Hamad; Ahmed, Abdulaziz; Ragheb, Gehan (Frontiers in Veterinary Science, 2020)
The SARS-Con-V2 crisis influenced all aspects of life in the country including academics, economics, medical, and other fields. Poultry industry, whether locally or globally, is one of the investment fields that has been affected by the current SARS-Con-V2 crisis. As part of this global world, the local poultry companies in Kuwait have been impacted by restricting movements and transportation of the employees in between the company branches, exportation and importation of goods, bank closures, rise in the imported and local vaccination and drug prices, sales and marketing. The current case study paper sheds light on the impact of the current SARS-Con-V2 crisis on the local poultry industry, as well as the challenges and gaps in the local poultry value chain. It also propose solutions to mitigate this impact and to enhance sustainability of poultry products during other future global or local crisis.